2013
DOI: 10.1186/1472-6831-13-34
|View full text |Cite
|
Sign up to set email alerts
|

The traditional practice of canine bud removal in the offspring of Ethiopian immigrants

Abstract: BackgroundThe custom of canine bud removal has detrimental consequences on children’s general health and dental care. The objective of this study was to assess whether the prevalence of missing primary canines and dental defects in offspring of emigrants from Ethiopia is greater than in offspring of native Israeli parents of similar socioeconomic class.Methods477 children of Ethiopian descent and 317 offspring of native Israeli parents, from 21 nursery schools and kindergartens, underwent dental examinations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 15 publications
(22 reference statements)
3
25
5
Order By: Relevance
“…Only three patients (0.85%) had maxillary canine removed, which is comparable with the study done in the offspring of Ethiopian immigrants in Israel (30), where only one upper canine was removed. The majority (69.89%) of the participants had bilateral mandibular canine mutilated, of which, 49.46% of them had missed canine in both sides.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Only three patients (0.85%) had maxillary canine removed, which is comparable with the study done in the offspring of Ethiopian immigrants in Israel (30), where only one upper canine was removed. The majority (69.89%) of the participants had bilateral mandibular canine mutilated, of which, 49.46% of them had missed canine in both sides.…”
Section: Discussionsupporting
confidence: 80%
“…The majority (69.89%) of the participants had bilateral mandibular canine mutilated, of which, 49.46% of them had missed canine in both sides. This finding is low compared with the finding in the offspring of Ethiopian immigrants (84.4%) of missed canine in both sides (30). This might be due to incomplete removal of the canine tooth bud during IOM due to some change in the use of materials during oral mutilation (like garlic rub) in the study area.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Among Ethiopian Jews who were airlifted into Israel in ‘Operation Solomon’ in 1991, extraction of canine buds was observed in 59% of children aged 3–12 years . This observation was corroborated and confirmed by a more recent study of native Israeli and children of Ethiopian parentage living under similar socio‐economic conditions, which compared 317 and 477 children, respectively, with regard to the presence of primary canines in two age groups (1.5–4 years and 4–7 years; . In both age groups, canines were seen among Israeli rather than among children of Ethiopian descent (87.5% vs. 42.3% in the younger group, 92.6% vs. 40.4% in the older group).…”
mentioning
confidence: 58%
“…However, a study on a group of children of Somali immigrants in England indicated that almost one third may have been subjected to IDE, and of those, 22% were born in England [8]. Prevalence as well as indication of continuance of IDE has also been reported in Israel [19,20].…”
Section: Introductionmentioning
confidence: 99%